Effects of Dose and Period of Neonatal Alcohol Exposure on the Context Preexposure Facilitation Effect - Murawski, Nathen J. (2011)
BACKGROUND: Alcohol exposure in the rat on Postnatal Days [PD] 4-9 is known to partially damage the hippocampus and to impair hippocampus dependent behavioral tasks. We previously reported that PD4-9 alcohol exposure eliminated the context preexposure facilitation effect (CPFE) in juvenile rats, a hippocampal-dependant variant of contextual fear conditioning. In the CPFE, context exposure and immediate shock occur on successive occasions and this produces conditioned freezing relative to a control group that is not preexposed to the training context. Here we extend our earlier findings by examining the effects of neonatal alcohol administered at multiple doses or over different neonatal exposure periods. METHOD: Rat pups (male and female) were exposed to a single binge dose of alcohol at one of three doses (2.75, 4.00, or 5.25g/kg/day) over PD4-9 (Experiment 1), or to 5.25g over PD4-6 or PD7-9 (Experiment 2). Sham intubated (SI) and undisturbed (UD) rats served as controls. On PD31, rats were preexposed to either the training context (Pre) or an alternate context (No-Pre). On PD32, rats received an immediate unsignaled footshock (1.5 mA, 2s) in the training context. Finally, on PD33 all rats were returned to the training context and tested for contextual freezing over a five-minute period. RESULTS: UD- and SI-Pre rats showed the CPFE, i.e., context preexposure facilitated contextual conditioning, relative to their No-Pre counterparts. The immediate shock deficit was present in all No-Pre groups, regardless of previous alcohol exposure. In Experiment 1, blood alcohol level was negatively correlated with contextual freezing. Group 2.75g-Pre did not differ from controls. Group 4.00g-Pre froze significantly less than Groups UD- and SI-Pre but more than Group 5.25-Pre, which showed the immediate shock deficit. In Experiment 2, alcohol exposure limited to PD7-9, but not PD4-6, disrupted the CPFE. CONCLUSIONS: This is the first demonstration of dose-related impairment on a hippocampus-dependent task produced by neonatal alcohol exposure in the rat. Exposure-period effects support previous studies of alcohol and spatial learning. The CPFE is a more sensitive behavioral task that can be used to elucidate developmental alcohol-induced deficits over a range of alcohol doses that are more relevant to human exposure levels.